PENGARUH BANTUAN DANA PENDIDIKAN TERHADAP INDEKS PRESTASI MAHASISWA FKIP UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - sihombing, Christina; Sianipar, Herlina Hotmadinar; Siahaan, Anton Luvi; Sinaga, Anggun Tiur Ida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of educational financial assistance (KIP-Kuliah) on the Grade Point Average (GPA) of students at the Faculty of Teacher Training and Education, Universitas HKBP Nommensen Pematangsiantar. The research applied a quantitative approach with a causal associative design. The population consisted of 135 students receiving KIP-Kuliah assistance, and all were selected as the sample using the total sampling technique. Data were collected through questionnaires and documentation and analyzed using validity and reliability tests, simple linear regression analysis, t-test, and coefficient of determination analysis. The results showed that the research instrument was reliable with a Cronbach’s Alpha value of 0.966. The regression analysis produced the equation (Y = 1.962 + 0.016X ), indicating a positive relationship between educational financial assistance and students’ GPA. The t-test result showed that the calculated t-value was higher than the t-table value (13.552 > 1.656) with a significance level of 0.001 < 0.05. Furthermore, the coefficient of determination (R²) was 0.580, meaning that educational financial assistance contributed 58% to students’ academic achievement. Therefore, educational financial assistance (KIP-Kuliah) has a positive and significant effect on students’ GPA. Keywords: KIP-Kuliah, educational financial assistance, student financial aid, academic achievement, higher education